101955 Bennu and 162173 Ryugu: Dynamical modelling of ejected particles to the Earth. (June 2020) - Kováčová, M.; Nagy, R.; Kornoš, L.; Tóth, J.
Abstract: Apollo-type asteroids Bennu and Ryugu are currently targets of sample-return missions. The goal of OSIRIS-REx mission (NASA) is to explore asteroid Bennu and Ryugu is being probed by JAXA's Hayabusa2 mission. Observations of Bennu in January 2019 revealed ejecting material in the close proximity of the asteroid. In this paper, we study orbital evolution of potential meteoroid streams along the orbits of Bennu and Ryugu by integrating over 5000 test particles each for 1000 y r . We searched for their approaches to the Earth and we were also interested in evolution of their Earth MOIDs in order to estimate possible activity of potential meteor showers. Our results indicate possible observability from the Earth approximately for next 400 − 500 y r in both cases. Theoretical radiants for both asteroids and their potential meteor showers were also calculated. Highlights: Ejected particles from Bennu and Ryugu are able to reach the Earth. Meteoroid streams originated from Bennu and Ryugu show possible present activity. The activity seems to last approximately for next 400–500 years. Related meteor showers have not been observed yet.